PENGARUH KUALITAS PRODUK DAN KEPERCAYAAN KONSUMEN TERHADAP NIAT BELI PRODUK DI SHOPEE (Studi Kasus Pada Pelajar SMP & SMA/Sederajat di Desa Leseng & Desa mokong Kec. Moyo Hulu) - Abdul Salam; Agustina A. Panambang (Journal of Management and Business, 2022)
This study aims to examine the effect of product quality on purchase intentions and consumer trust on purchase intentions at shopee. The variables used in this study are Product Quality and Consumer Trust as independent variables, and purchase intention as the dependent variable. This research uses quantitative methods. The number of samples used in this study was 100 respondents. By taking samples using the purposive sampling technique method. The method of data collection is done using a questionnaire. This research the see the multiple Linear Regression analysis techniques using SPSS software analysis tool version 16.0 for windows. The results of the analysis in this study indicate that (1) Product Quality Variable has a significant effect on Purchase Intention with a calculated r-value of 4.039 which is greater than t table 3.97 with a significance value of 0.000 less than 0.05. (2) The Consumer Confidence variable has a significant effect on Purchase Intention with a calculated r-value of 4.27, which is greater than t table 3.97 with a significance value of 0.012, which is smaller than 0.05.